The Role of Leadership, Work Discipline, and Training in Enhancing Employee Performance: Evidence from the Communication and Information Office of Papua Province - Lakehu, Hasanudin; Kambu, Arius Andreas; Erari, Anita (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
This study examines the influence of leadership, work discipline, and training on employee performance at the Communication and Information Office of Papua Province. A survey was conducted using a structured questionnaire distributed to 92 respondents, and the data were analyzed using multiple linear regression. The results reveal that leadership, work discipline, and training collectively have a significant effect on employee performance. Partially, leadership and work discipline significantly influence performance, while training does not show a significant effect. Among the three variables, work discipline emerges as the most dominant factor affecting employee performance. These findings imply that enhancing employee performance requires strengthening leadership practices and work discipline, while training programs should be restructured to ensure greater effectiveness.